Economics and Law - Bychenok I. A., Pichugin A. P., Stadnik A. T., Vartanova M. L., Kostygova L. A., Kruglov V. N., Tyutin D. V., Mironova N. G., Orlova T. S., Chuiko E. A., Iakhiaev D. B., Grigorishchin A. V., Siluanova L. S., Arbekova V. V., Ivanova E. N., Riaguzova T. A., Savchenko D. A. (Economics and Law, 2021)
the article analyzes the state of demographic indicators, еmployment and unemployment in rural municipalities of the Novosibirsk region. It is shown that the economic stability of rural areas is to some extent related to the effectiveness of using the opportunities of socially oriented non-profit organizations (NPOs), whose activities can significantly reduce the negative manifestations of the budget deficit. Based on statistical data, rural municipal districts were ranked according to the degree of population loss. This allowed us to identify the correlation between demographic parameters and the activity of work in rural areas for the organization of so-called NGOs with applications and grant support. The degree of activity and effectiveness of socially-oriented NGOs in the manifestation of demographic indicators in areas, as well as their positive impact on reducing tension in society. The solution of employment issues of the rural population, including pensioners, ensures the progressive movement of territories to progress by involving the population in active labor and creative life.
Keywords: employment; некоммерческая организация; демографические показатели; занятость населения; сельское население; rural population; корреляционная зависимость; ранжирование территорий; экономическая эффективность деятельности НКО; demographic indicators; correlation dependence; ranking of territories; non-profit organization; economic efficiency of NPOs